Cost-effectiveness of Laboratory Monitoring in Sub-Saharan Africa: A Review of the Current Literature - Walensky, Rochelle P. (2010)
As the global community evaluates the unprecedented investment in the scale-up of HIV therapy and considers future investments in HIV care, it is crucial to identify those HIV interventions that maximize the benefit realized from each dollar spent. The use of laboratory monitoring assays – CD4 cell count and HIV RNA – in decisions about when to initiate and switch antiretroviral therapy may offer substantial clinical benefit, but their economic value remains controversial. Cost-effectiveness analysis can be used to evaluate the value for money of strategies for HIV care, including alternative approaches to laboratory monitoring. Five published cost-effectiveness analyses address the question of CD4 and HIV RNA monitoring for HIV-infected patients in Africa, with differing conclusions. We describe the use of cost-effectiveness analysis in resource-limited settings and review the cost-effectiveness literature with regard to CD4 and HIV RNA monitoring in Africa, highlighting some of the most critical issues in this debate.